Challenges and Opportunities of English Grammar Acquisition by Distance at the Tertiary Level - Monta Farneste; Vineta Apse (Baltic Journal of English Language, Literature and Culture, 2021)
Distance learning introduced in almost all educational establishments in spring 2020 has raised interest among researchers how to deal with it in a more productive way. Thus, the goal of the research was to find out undergraduates’ views on distance learning of English grammar and the use of online revision materials in developing students’ independent study skills at a tertiary institution in Latvia. the research tool was a questionnaire consisting of open-ended and closed questions. Twenty-three students answered the survey questions. the research results indicate that studying by distance is preferred because it allows the students to choose the study time and place, to develop their timemanagement, independent study skills, as well as improve their motivation. the main drawbacks of studying by distance, according to the students, are insufficient feedback, inability to ask questions directly and receive immediate answers and problems with their own time management and independent study skills.